Вплив кореляції імпульсів на властивості фрагментів, народжених у зіткненнях важких іонів - Gautam, S.; Kant, R. (Publishing house "Academperiodika", 2012)
We study the effect of momentum correlations on the properties of light and medium mass fragments by imposing the momentum cut in clustering the phase space. The rapidity distributions, dN/ptdpt spectra, and ratio of transverse to longitudinal energy (Erat) for the reactions of 12C+12C and 40Ca+40Ca are analyzed. We have found a significant influence of the momentum cut on these properties of the fragments. The results of our calculations are compared with experimental data.